Estimating the health and economic burden of shipping related air pollution in the Iberian Peninsula. (November 2021) - Nunes, Rafael A.O.; Alvim-Ferraz, Maria C.M.; Martins, Fernando G.; Peñuelas, Antonio L.; Durán-Grados, Vanessa; Moreno-Gutiérrez, Juan; Jalkanen, Jukka-Pekka; Hannuniemi, Hanna; Sousa, Sofia I.V.
Highlights: Shipping air pollution is a considerable burden affecting the Iberian Peninsula. PM2.5 ship-related emissions increased all-cause premature deaths by 7.7%. NO2 ship-related health impacts were similar to those of PM2.5 . Morbidity costs represented around 12–15% of the total costs estimated. Implementing measures to mitigate shipping air pollution in this region is needed. Abstract: Air pollution is the leading cause of the global burden of disease from the environment, entailing substantial economic consequences. International shipping is a significant source of NOx, SO2, CO and PM, which can cause known negative health impacts. Thus, this study aimed to estimate the health impacts and the associated external costs of ship-related air pollution in the Iberian Peninsula for 2015. Moreover, the impact of CAP2020 regulations on 2015 emissions was studied. Log-linear functions based on WHO-HRAPIE relative risks for PM2.5 and NO2 all-cause mortality and morbidity health end-points, and integrated exposure–response functions for PM2.5 cause-specific mortality, were used to calculate the excess burden of disease. The number of deaths and years of life lost (YLL) due to NO2 ship-related emissions was similar to those of PM2.5 ship-related emissions. Estimated all-cause premature deaths attributable to PM2.5 ship-related emissions represented an average increase of 7.7% for the Iberian Peninsula when compared to the scenario without shipping contribution. Costs of around 9 100 million € yr-1 (for value of statistical life approach - VSL) and 1 825 million € yr −1 (for value of life year approach - VOLY) were estimated for PM and NO2 all-cause burden of disease. For PM2.5 cause-specific mortality, a cost of around 3 475 million € yr −1 (for VSL approach) and 851 million € yr −1 (for VOLY approach) were estimated. Costs due to PM and NO2 all-cause burden represented around 0.72% and 0.15% of the Iberian Peninsula gross domestic product in 2015, respectively for VSL and VOLY approaches. For PM2.5 cause-specific mortality, costs represented around 0.28% and 0.06%, respectively, for VSL and VOLY approaches. If CAP2020 regulations had been applied in 2015, around 50% and 30% respectively of PM2.5 and NO2 ship-related mortality would been avoided. These results show that air pollution from ships has a considerable impact on health and associated costs affecting the Iberian Peninsula.